CATing the Way: Polish Translators and Computer-Assisted Translation Tools - Organ, Michał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
This paper aims to establish a profile of Polish translators who apply CAT tools in their professional practice. The investigation identifies six primary categories, shedding light on the translators themselves, their experience, and interactions with specialised software. The first category delves into demographic data, analysing age groups and gender distribution among the users. The second category focuses on basic data encompassing the translators' experience with programs and their preferred foreign languages. The paper also explores the link between higher education and CAT tool proficiency, examining fields of study, educational institutions, specialised training, and opinions on the integration of this technology into academic curricula. In order to assess the non-academic aspects of learning and applying such software, it investigates the translators' engagement in training courses, certifications, and sources of qualifications improvement. Various methods for acquiring skills in CAT tools are also explored, such as online webinars and practical translation practice. The results reveal that the translators are rather experienced users of the software, they rely heavily on such programs, employing them in various types of translations, mostly non-literary texts. Translators perceive them positively, acknowledging their contribution to accelerating work processes and improving competitiveness in the translation market. The use of CAT tools is expected to increase, emphasising the need to incorporate these tools into translator training programs and adapt study plans to accommodate their further popularisation. The data was collected through an anonymous survey and provides insights into the preferences, habits, and perspectives of Polish translators using CAT tools. This paper serves as a foundation for further research and comparison with other translator groups, contributing to a more comprehensive understanding of the translator's profession in the context of translation technology utilisation.
Keywords: CAT tools; computer assisted translation; translator; translation technology